Hubungan antara Keyakinan Mahasiswa Akuntansi terhadap Pengetahuan dengan Kinerja Ujian Multiple Choice dan Essay - Silvi, Alfiati (Jurnal Akuntansi dan Bisnis, 2004)
The sophisticated beliefs toward knowledge dan learning are important in order to increase student’s ability to act profesionally in the future. Previous empirical research show that the sophisticated beliefs about knowledge dan learning influencing student’s performance. The objectives of this research are to examine the accounting student’s beliefs toward knowledge dan learning, dan the relation between these beliefs dan student performance. The research methods used in this study are questionaire dan exam questions. 174 students are participating in this research. The results show that beliefs about the uncertain knowledge, the complex knowledge, learning gradually dan unlimited capacity do not affect student’s performance on multiple choice test. On the other hand, beliefs about the uncertain knowledge, the complex knowledge, and the unlimited knowledge capacity affect student’s performance on essay test positively. But, beliefs about learning gradually do not affect student’s performance on essay test.